(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
High performance thin layer chromatographic method was described for the analysis of mefenamic acid, paracetamol and dicyclomine HCl in tablet dosage form. The method employed HPTLC aluminium plates precoated with Silica gel 60F254 as the stationary phase and mixture of Toluene: Acetone: Formic acid (10:9.8:0.2) as mobile Phase. The densitometric evaluation of separated bands was carried out at 254 nm for mefenamic acid and paracetamol. In method development, Dicyclomine HCl was not detected in UV absorbance at 254 nm, so that same plate was poured in dragandroff reagent and measured at 510 nm wavelength. The linear response was observed in range of 100-700 ng/spot with correlation coefficient of, 0.998, 0.997 and 0.978. Precision was found to be within limits. The percentage recovery was found to be the limits of acceptance criteria between the range of 99.03% to 101.24%.